Handbook of differential equations : stationary partial differential equations. - Chipot, M. (Michel) (Elsevier, 2008)
A collection of self contained state-of-the art surveys. The authors have made an effort to achieve readability for mathematicians and scientists from other fields, for this series of handbooks to be a new reference for research, learning and teaching. * Written by well-known experts in the field * Self contained volume in series covering one of the most rapid developing topics in mathematics * Informed and thoroughly updated for students, academics and researchers.